Kebijakan Hukum Terhadap Penanganan Pandemi Covid-19 di Indonesia - Putu Sekarwangi Saraswati (Kertha Wicaksana, 2020)
The Covid-19 pandemic has become very dangerous because it is transmitted so quickly and caused the death of many lives in the world. The Government and the National Disaster Management Agency have coordinated with local governments to carry out disaster management by issuing social distancing and physical distancing policies. Many PSBB policies are ineffective because surely the community feels that they have not yet fully received legal protection for the existing policies made by the government at this time. To avoid another level of infertility, the following efforts were made so that the PSBB policy provided during the effective pandemic period in accordance with the 1945 Constitution of the Republic of Indonesia, among others, the Central Government and Regional Governments ensures the disclosure of public information in order to be able to find out the chain of the virus spreading. The government must be able to guarantee and ensure especially to the lower middle class are able to meet their needs to guarantee the right to life of their people and not diminished any dignity of the people (in accordance with the mandate of the 1945 Constitution of the Republic of Indonesia) and the need for a public role in terms of mutual care, mutual reminding, and help each other. This article will continue to be discussed using a literature approach in which the writer will use primary sources in the form of literature books that have to do with the problems to be examined. The things that occur in the field can be seen that the legal policy decided by the government during the pvidemic co-19 period has apparently not been implemented properly as mandated because there are still many people who violate the PSBB activities proclaimed by the government even though criminal sanctions have been regulated by very clear.